The Influence of Employee Motivation on Operational Efficiency at Electricite du Laos (EDL), Oudomxay Province Branch - Souliya, Khamloun; Duangvilaykeo, Thipphavanh; Sifongxay, Sangthong (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This research aims to study motivation for work performance of employees in Lao Electric Power Company, Oudomxay Province Branch; To study the efficiency of work performance of employee in Lao Electric Power Company; and to study the motivational factors and hygiene factors that affect the performance of the Lao Electric Power Company. This study is a quantitative study using a questionnaire to collect data from a sample of 184 employees. Data analyzed the data using the Statistical Package for Social Sciences program to process descriptive statistics and Inferential statistics. The results found that work motivation among employees is about compensation and welfare benefits, including the appropriateness of annual salary increases, the adequacy of salaries in relation to the cost of living, and the suitability of bonuses provided to employees. In addition, motivation related to career advancement was also identified as an important factor. This included opportunities for career progression within employees’ current positions, recognition of performance based on work achievements, consideration for promotion, fair and appropriate internal promotion processes, and support from supervisors. Furthermore, the efficiancy of employee work at Electricité du Laos in the Oudomxay provincial branch indicated in good quality, particularly evident in terms of time management in completing tasks, the quality of work, and the quantity of work accomplished. The factors influencing job performance revealed that achievement-related factors, responsibility, job security, and the work environment significantly affected the work performance of employees at Electricité du Laos, Oudomxay branch. These factors demonstrated a statistically significant relationship with job performance at the 0.05 significance level.